2009
DOI: 10.1111/j.1365-294x.2009.04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale comparative phylogeography of a sympatric sister species triplet of subterranean diving beetles from a single calcrete aquifer in Western Australia

Abstract: Calcrete aquifers in the arid Yilgarn region of central Western Australia are a biodiversity hotspot for stygofauna. A distinct pattern of interspecific size class variation among subterranean dytiscid beetle species has been observed in 29 of these aquifers where either two or three small, medium and/or large sympatric species are found that are in some cases sister species. We used a 3.5 km(2) grid of bores to sample dytiscids on a fine-scale and employed a comparative phylogeographical and population geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 89 publications
9
61
0
Order By: Relevance
“…A repeated pattern of two to three species of stygobiontic diving beetles is consistently observed within isolated aquifers, some of which are clear sympatric sister species (Leys et al, 2003;Watts and Humphreys, 2006;Guzik et al, 2009). To date, this pattern has been observed in 29 calcretes in which each species occupies non-overlapping size classes, ranging from large (B5 mm) to very small (B1 mm) beetles (Watts and Humphreys, 1999, 2003, 2006.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A repeated pattern of two to three species of stygobiontic diving beetles is consistently observed within isolated aquifers, some of which are clear sympatric sister species (Leys et al, 2003;Watts and Humphreys, 2006;Guzik et al, 2009). To date, this pattern has been observed in 29 calcretes in which each species occupies non-overlapping size classes, ranging from large (B5 mm) to very small (B1 mm) beetles (Watts and Humphreys, 1999, 2003, 2006.…”
Section: Introductionmentioning
confidence: 94%
“…However, given the extraordinary number of species observed in cave systems (Poulson and Culver, 1969;Humphreys, 2000Humphreys, , 2008Buhay et al, 2007), this transition, from surface to subterranean environments, is unlikely to be the sole source of species diversification in cave animals and it is possible that some species evolved from troglomorphic ancestors fully adapted to life underground (Juan and Emerson, 2010;Ribera et al, 2010). The difficult nature of gaining access to cave habitats makes this latter hypothesis difficult to investigate; however, a number of key studies have examined these questions (Caccone, 1985;Buhay and Crandall, 2005;Guzik et al, 2009). They observe that, internally, cavernicolous habitats maintain complex genetic systems that, undisturbed, are largely stable over time and can maintain significant levels of genetic diversity (Culver, 1970a, b;Culver et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonisation of these habitats by multiple unrelated surface species has also contributed to the high levels of diversity (Leys et al 2003;Cooper et al 2008;Guzik et al 2008). Further, in situ speciation within aquifers is also considered a plausible source of species diversity, particularly in the Yilgarn (Guzik et al 2009;Juan et al 2010) and Pilbara (Finston et al 2009). Abiotic heterogeneity within habitats (i.e.…”
Section: The Predicted Origins Of This Diversitymentioning
confidence: 99%
“…In the Yilgarn and Pilbara regions a myriad of short-range endemic species, including both stygobitic (Taiti and Humphreys 2001;Leys et al 2003;Leys and Watts 2008;Page et al 2008;Guzik et al 2009;Bradford et al 2010) and troglobitic (Humphreys and Adams 2001;Harvey et al 2008) taxa have been identified. Much of this diversity is likely to have resulted from vicariance associated with the aridification of the Australian continent after the late Miocene (Byrne et al 2008), which led to biotic isolation of calcretes and other subterranean habitats (e.g.…”
Section: The Predicted Origins Of This Diversitymentioning
confidence: 99%